2020
DOI: 10.3389/fphy.2020.00246
|View full text |Cite
|
Sign up to set email alerts
|

Triple Diffusive Unsteady Flow of Eyring–Powell Nanofluid Over a Periodically Accelerated Surface With Variable Thermal Features

Abstract: This research communicates the triple diffusion perspective of Eyring-Powell nano-materials configured by a periodically moving configuration. The thermal consequences of variable natures are utilized as a novelty. Combined magnetic and porous medium effects are also involved, which result in a magneto-porosity parameter. The thermophoretic and Brownian motion aspects are reported by using Buongiorno's nanofluid theory. The formulated flow equations in non-dimensional forms are tackled with the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This compelling situation is the time-dependent flow for which diverse features of fluid locomotion may be scrutinized at different times. This notion was pioneered by Wang 35 and extended by several researchers 28,[36][37][38][39][40][41][42][43][44] for various non-Newtonian fluids. Ali et al 36 scrutinized the MHD flow of viscoelastic fluid over a periodically accelerating surface with extrinsic features, including porous media and cross-diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compelling situation is the time-dependent flow for which diverse features of fluid locomotion may be scrutinized at different times. This notion was pioneered by Wang 35 and extended by several researchers 28,[36][37][38][39][40][41][42][43][44] for various non-Newtonian fluids. Ali et al 36 scrutinized the MHD flow of viscoelastic fluid over a periodically accelerating surface with extrinsic features, including porous media and cross-diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad et al 40 explored the unsteady flow of Oldroyd-B fluid induced by periodically moving heated surface considering heat generation/absorption which was found to efficiently upsurge thermal field. Khan et al 41 reported on the triplediffusive unsteady flow of Powell-Eyring nanofluid induced by accelerated and periodically moving surface accounting for the collective impact of the porous medium and magnetizing field intensity. It was found that increment in magneto-porosity parameter demonstrates diminishing behavior in the periodic oscillation of velocity along with its magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [25] explored the thermal Eyring-Powell nanoliquid with triple diffusion via a periodic-moving system. A combination of some important parameters, such as the porosity parameter and magnetic effect, was also discussed.…”
mentioning
confidence: 99%